Protection and improvement of the environment in Colombia (2014)
This document invites man to reflect on the care, protection and improvement of the environment, it is our duty to defend it at all costs, because the preservation of the human species depends on the ability of the man to solve the problems that have arisen over time due to lack of awareness we have come to exceed the limits, because of the ambition of owning property and being at the forefront of a metallized globalization. The sense of responsibility, leading to a desperate search to find immediate solutions to solve the problems that currently exist, in order to prevent future, other problems that may be of higher incidence, which definitely affect our environment.